The Link Between Multicultural Experiences and Creative Performance: A Meta-Analysis - Khoiriyah Khoiriyah; Ethan Tan; Ryan Teo (Yayasan Adra Karima Hubbi, 2025)
Multicultural experiences have increasingly been recognized as a catalyst for creativity by expanding cognitive flexibility, perspective-taking, and integrative thinking. However, empirical findings on the strength and consistency of this relationship remain fragmented across studies. This research aims to synthesize existing evidence through a meta-analysis examining the link between multicultural exposure and creative performance. A total of 68 peer-reviewed studies (N = 12,457 participants) were systematically selected from major academic databases, including Scopus, Web of Science, and PsycINFO. Effect sizes were computed using a random-effects model to account for cross-study heterogeneity. Moderator analyses explored contextual factors such as type of multicultural experience (living abroad, cross-cultural training, or diversity interaction), creativity domain (divergent thinking, creative problem-solving, and innovation), and cultural distance. The meta-analytic results revealed a moderate positive effect size (r = 0.34, p < 0.001), indicating that individuals with higher levels of multicultural exposure consistently demonstrate enhanced creative performance. Living abroad showed the strongest effect among all experience types, particularly in tasks involving divergent and integrative thinking. The findings confirm that multicultural engagement fosters creativity by broadening cognitive schemas and enhancing openness to novelty.